Peningkatan keterampilan renang gaya bebas menggunakan metode drill dengan media pelampung dan fins - Ramadhan, Imam; Nur, Suaib; Ahmad, Ahmad (Jurnal Porkes, 2023)
This research aims to determine the I,provement of freestyle swimming skills using the drill method whit buoys and fins as media.This study uses experimental research methods.Then the design in this study was pre-eksperimental design with the form of the  one group pretest and posttest.the sampling technique in this study was total sampling because the sampling technique for this study involved some members of the population used as samples.the sample used in this study was 10 students from the garuda laut clib palopo.The results showed that there was an increase in the average score of the students from the pretestand posttest,namely,and 10,80 to 17,80, based on the normality test results of the pretest and posttest above the significant value , so it can be concluded that the pretest and posttest is normally distributed.based on the output paired sample test,it is known that the difference between the average pretest and posttest = 7,000 standard deviation = 0,667.from the SPPS output ,Tcount = 33,204 Ttable 2,306.When viewed from the significance,that the sig(2-tailed) value is 0,001. Because the significance values is less than (α 0,05), then Ho is rejected and Ha is accepted.So it can be concluded that there is significant effect of the drill methodusing buoys and fins media on freestyle swimming skills for beginners at Garuda Laut Club palopo